BEGINNING OF E-COMMERCE ERA IN ETHIOPIA - Theodros Tiruneh, Manish Kumar Mishra (International Journal of Advanced Science and Technology, 2020)
The growth of the Information and Communication Technology (ICT) continues to have a tremendous influence on business. Companies and organizations of all types and sizes are rethinking their strategies and how they run their operations in this ICTs era. Electronic commerce or E-commerce, one of the most dynamic applications of ICT, is growing rapidly throughout the world. It plays a significant role in the development and economic growth of country. In Ethiopia, E-commerce is in its beginning phase. To make e-commerce successful, business organizations should be encouraged to use latest technology oriented environment. Lacks of experienced labors, improper technical infrastructure are some challenges faced by organizations when they start e-commerce in Ethiopia. In this paper an attempt has been made to assess the impact and challenges of E-commerce in Ethiopia. The initiatives that should be taken by the Government and the organizations to make it successful are also analyzed.